Implementasi Algoritma Traveling Salesman Problem (TSP) dalam Penentuan Jalur Terpendek pada Rute Berlayar untuk Kegiatan Aplousing dan Perawatan SBNP di Wilayah Kerja Kantor Distrik Navigasi Tipe A Tanjung Perak: Penerapan Model TSP dalam Efisiensi Operasional Maritim - EFENDI, ADE IRFAN (Program Studi Teknik Informatika Universitas Pamulang, 2025)
This study aims to optimize routes to improve fuel efficiency and voyage time, as well as reduce environmental pollution from state ship operations in Aplousing and Navigation Aid Maintenance (SBNP) activities in the working area of the Tanjung Perak Type A Class I Navigation District. To achieve this objective, the Traveling Salesman Problem (TSP) algorithm was applied to determine the shortest route connecting 11 port locations and islands in the waters of East Java. Two algorithmic approaches proposed in this study are the Heuristic Nearest Neighbor and Brute Force methods. Simulation results show that the Brute Force approach produces the most optimal route with a total distance of ± 1,095.94 km, which is more efficient than the Heuristic Nearest Neighbor approach at ± 1,110.33 km and the initial route without optimization at ± 1,284. The reduction in distance traveled has a positive impact on reducing fuel consumption, sailing time, and exhaust emissions. This study demonstrates that the application of the TSP algorithm can improve operational efficiency in shipping and can serve as a foundation for developing technology-based decision support systems for more environmentally friendly shipping route management.